The Implementation of Indonesian Language Learning for Dyslexic in Children at Elementary Schools in Bengkulu - Heny Friantary; Zelvia Liska Afriani; Yuni Nopitasari (Islamic State Institute of Bengkulu (IAIN) Bengkulu, 2020)
This research is motivated by Indonesian language learning which requires each student to master four language skills, namely listening, speaking, reading and writing. In children with dyslexia or reading difficulties, the implementation efforts made by the 7th grade teacher of the Bengkulu City Special School 05 so that the child continues to master language skills despite having difficulty reading. This study aims to describe the methods used by teachers in Indonesian language learning so that dyslexic children can master reading skills. This type of research is descriptive qualitative research. Data collection techniques used were observation, interviews, and documentation. Meanwhile, the data analysis techniques used were data reduction, data presentation, and finally verification. The results of the study concluded that the implementation of learning in dyslexic children was preparation, implementation, and evaluation. The Indonesian language learning method used by the 7th grade teacher of SLB N 05 Bengkulu City in dyslexic children is the lecture method, the audiolingual method, the skimming method, and the picture and picture cooperative method.